The public affairs faculty manual a guide to the effective management of public affairs programs - McDonald, Bruce D.; Hatcher, William Scott 1980- (Routledge, 2020)
"While public affairs faculty study administration and management techniques, few administrators of public affairs programs receive formal training in the nuts and bolts of academic administration. Even those faculty who come to the academia after distinguished careers in managerial positions may not be ready for the very different (and difficult) environment of university administration. The Public Affairs Faculty Manual argues that public affairs as a field needs to ensure that knowledge about administration and management is applied to the running of its academic programs, and brings together major leaders in the discipline to explore key features of academic administration. Many of these leaders have served as MPA directors, chairs, and deans at the nation's topic public affairs programs. Crucial issues of academic administration discussed include the basics of public affairs programs, models of governance, roles of different administrative leaders, planning and budgeting for programs, navigating the accreditation process, assessing and improving student learning, ensuring social equity and cultural competency, mentoring faculty, developing curriculum, and helping provide service and applied research to community partners. Themes running throughout the book's chapters are examined, and additional resources to help manage public affairs programs are offered. The collection and the strategies within it are designed to encourage faculty to assume positions of leadership in their programs and manage those programs in an effective, efficient, and fair manner. The Public Affairs Faculty Manual is required reading for new, seasoned, and aspiring academic administrators in public administration, public policy, and nonprofit management programs, as well as schools of government"--
Description based on online resource; title from digital title page (viewed on April 21, 2020)
Keywords: Political science / Study and teaching (Higher) / United States; College department heads / United States / Handbooks, manuals, etc; College administrators / United States / Handbooks, manuals, etc; Universities and colleges / United States / Administration / Handbooks, manuals, etc